Beyond nationalism? The inter-war period and some features of the complex transformation of southeastern Europe - Basciani Alberto (Balcanica)
In Southeastern Europe, the end of the First World War marked a profound geopolitical transformation and the start of an important and conflicting process of modernisation of the economic, social and political structures of the countries in the region. Agrarian reforms, changes in political structures, increasing urbanisation, population growth, and ad hoc legislation for minority rights protection were some of the most important issues addressed in those years. This essay aims to elucidate the main knots and contradictions in the internal and international life of the countries of Balkan Europe, showing how efforts to change political and social structures encountered enormous obstacles in the intrinsic weakness of those socio-economic structures, but also in the will of important segments of the Balkan ruling classes, especially those who had realised the nationalistic dreams of the decades before the Great War, to reassert the supremacy of their respective power and ethnic groups. Yet there were changes, and important ones at that. In foreign policy, for example, the Balkans was the only region in Europe where an attempt was made to turn the so-called ‘spirit of Locarno’ into a concrete achievement, albeit unsuccessfully.